The Influence of Content Marketing on Patient Loyalty by Mediating Intention to Follow and Brand Trust - Luthfi Faishal Fauzi; Yani Nurhadryani; Jono Mintarto Munandar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
During the pandemic, the hospital industry is an industry that must adapt to the digital world. Hospital X is a hospital that is active on social media and has several followers which is quite high, but it turns out that it is not in line with the BOR achievement. This can be caused by many factors such as content marketing, the relationship between the number of followers, brand trust, and brand loyalty. Data were collected from 125 respondents. Data were analyzed using WarpPLS. The results showed that the majority of respondents consisted of young families with middle incomes. Then it was found that content marketing had a significant effect on brand trust and brand loyalty. Based on this, hospitals should focus more on high-quality content that aims to increase patient trust.